A Computational Study on the Antioxidant Activity of Certain Random Copolyesters Containing Bis(arylidene) Cycloalkanone Moiety in the Main Chain - Kiruba, B.; Chidambaravinayagam , S. (Journal of Scientific Research, 2023)
A series of five random copolyesters was synthesized by polycondensation of different arylidene diols with curcumin as a common diol and a common diacid chloride in the ratio of 1:1:2, respectively. The five arylidene diols were synthesized by an acid-catalyzed Claisen condensation reaction. The repeating units present in these five random copolyesters and also the backbone was identified by FT-IR, 1H-NMR, and 13C-NMR spectroscopic techniques. The curcumin based copolyester exhibited good antioxidant activity, confirmed by various antioxidant activity determinations. Structural analysis such as HOMO and LUMO energies and the HOMO-LUMO energies gap of the molecule has been calculated using the B3LYP/6-311+G (d, p) level of theory. The antioxidant property of the molecule can be explained by the hydrogen atom transfer by theoretical study.